Dampak Integrasi Technological Pedagogical Content Knowledge dan Ice breaking dalam Pengajaran Literasi Baca dan Tulis di Sekolah Dasar - Haifaturrahmah, Haifaturrahmah; Muhdar, Syafruddin; Bilal, Arpan Islami (Bima Journal of Elementary Education, 2024)
This study aims to analyze the impact of integrating Technological Pedagogical Content Knowledge (TPACK) and ice breaking in teaching reading and writing literacy at the elementary school level. Employing a quantitative approach with a quasi-experimental design, the research involved fourth-grade students from SDN Mataram Regency, divided into experimental and control groups. Data collection instruments included literacy tests and observation sheets measuring student engagement. The results revealed that the experimental group receiving instruction with integrated TPACK and ice breaking showed a significant improvement in literacy scores, with an average increase of 31.2%, compared to only 11.7% in the control group. Furthermore, this integration enhanced student engagement during the learning process. In conclusion, the TPACK and ice breaking approach not only improved students' academic outcomes but also created a more interactive and enjoyable learning environment. This study recommends adopting this strategy as an innovative solution to enhance literacy quality in elementary schools, particularly in Indonesia.